“Kotak Pikiran Positif” Untuk Menumbuhkan Kebahagiaan dan Optimisme Pada Anak TPQ Chasan Puro - Khoirina Ayudia Putri; Shofi Zakiyyah Jasri; Karirotul Uyun, Novia; Nadya Aditya Ningrum; Qonita Mustika Bilqis; Dewi Khurun Aini (PUSAKO : Jurnal Pengabdian Psikologi, 2024)
Happiness and optimism are important during children's growth and development. This study aims to find out how to regulate emotions and increase optimism. The participants of this research are children of TPQ Chasan Puro. This research uses a Participatory Action Research (PAR) approach with the positive mind box method. In this method, TPQ children write their hopes, feelings or positive affirmations. The pretest showed that most children tended to harbor emotions and lacked an optimistic attitude when facing a challenge. After being given psychoeducation, there was an increase in the ability to express emotional feelings and self-confidence. The research proves that this program is effective in building a learning atmosphere that fosters happiness, optimism and emotional development in children.